PENERAPAN ANGGARAN SEBAGAI ALAT BANTU MANAJEMEN PADA PT. POS INDONESIA KANTOR AREA X MAKASSAR - Neng Indriyani (AkMen JURNAL ILMIAH, 2015)
The aim of this research study to determine whether the procedure of preparation of the Budget on PT. Pos Indonesia has. While the methods of analysis used in this research is the analysis of variance, which is to know the actual results with budgeted plan by comparing the revenue budgeted against actual income of the same. The results of this study were (1) the budget prepared by PT. Pos Indonesia (Persero) is expressed in monetary units Rupiah shaped both in terms of budget revenue. (2) The proposed budget is discussed and approved by the higher authorities in accordance with the company's organizational structure. (3) Revenues are recorded in the proper account time for their account numbering conducted by PT. Pos Indonesia (Persero) on each budget item facilitate the performance of employees so that it can be said sufficient.